A representatividade LGBT na história em quadrinhos heartstopper - RODRIGUES, Anderson dos Santos (2024)
Addressing and/or discussing issues related to sexuality in any setting or environment is still taboo these days. In educational institutions, for example, content related to sexuality is rarely put on the agenda, with a lack of knowledge and interest being the main reasons for this. However, it is becoming increasingly important and necessary to address these issues, such as LGBTQIAPN+ issues, given all the violence these people suffer on a daily basis. Talking about the subject is necessary because, among other things, it spreads information about it and, directly or indirectly, contributes significantly to breaking down prejudices and inequalities. So, in view of these issues, the main objective of this work is to address the current condition of the LGBTQIAPN+ community, in order to identify how characters who fit into the movement are portrayed in fiction, using Heartstopper comics as the object of study. To this end, the work initially starts with bibliographical research, based on the works of Cirne (1982), Guedes (2007), Leite (2019), and the like. There is also a qualitative analysis of the first two volumes of Heartstopper comics. At the end of the work, it was concluded, among other things, that LGBTQIAPN+ representation within the comic is seen at different times and in different ways, whether in male or female homosexual relationships.